Preliminary study on e-hailing drivers needs in English language learning for the purpose of successful communication in tourism industry / Shahazwan Mat Yusoff, Anwar Farhan Mohamad Marzaini and Siti Maftuhah Damio - Mat Yusoff, Shahazwan; Mohamad Marzaini, Anwar Farhan; Damio, Siti Maftuhah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
E-hailing apps Grab and Uber have become household names, particularly among urbanites over these five years. Overall the consumer response to e-hailing services in Malaysia has been positive, with The Land Public Transport Commission (SPAD) reporting that 80% of consumers prefer e-hailing over taxis. As such, many believe the availability of e-hailing services will help to boost demand, and raise property prices and rentals and help the tourism sector in locations where they are available. As the demand grows, and tourists around the globe keep rising, the means of communication plays a vital role. Hence, this article explores the Grab drivers' needs in English language learning for the purpose of successful communication in working environment. The needs are categorised into three elements: needs of English language at workplace, problems in English language usage, and preferences in learning English. A case study was carried out among 50 Grab drivers in Kuala Lumpur. The analysis of responses to the needs in English language learning among Grab drivers is hoped to fashion English language course or the syllabus to the e-hailing drivers.